Optimum Equivalent Loading in Multi-Dimensional Transmission - Cioffi, John M.; Chow, Peter S.; Kerpez, Kenneth J. (IEEE open journal of the Communications Society, 2020)
Loading methods for wireline and wireless transmission systems are explained and reviewed to allow examination of fundamental equivalences between approaches to optimum transmission with linear cross-dimensional interference. Shannon's famous water-filling method is then re-interpreted by examining the difference between mutual information and the constellation size used on each tone. Results reinforce that highest performance in all methods retains use of Shannon's water-filling. However, results also find that a constant-size constellation on all energized water-filling dimensions, when used with a good code and an appropriate joint maximum-likelihood decoder, is sufficient to approximate this highest performance. This means that tone-dependent constellation variation is not necessary, which increases receiver complexity but reduces the need for channel-state feedback. This then leads to some adaptive MCS (modulation and coding scheme) equivalent loading methods that can be applied generally to wireline and wireless transmission.